2002
DOI: 10.1007/s00421-002-0595-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β1-selective adrenergic blockade on maximal blood lactate steady state in healthy men

Abstract: The aim of this study was to compare the effect of taking bisoprolol (B), a highly beta(1)-selective adrenoceptor antagonist to that of a placebo (P) on maximal lactate steady state (MLSS), which reflects the transition from oxidative to partially anaerobic metabolism. Ten healthy male subjects [mean (SD) age 23 (3) years, height 181 (6) cm, body mass 76 (6) kg] randomly received oral P or B (5 mg x day(-1)) for 2 weeks using a double-blind crossover design. In the 2nd week, the subjects performed an increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…During steady-state exercise, this leads to an equilibrium in BL appearance and BL elimination. The highest workload, which can be performed for about 30 min without a systematic increase in the BL concentration, is called 'maximal lactate steady state' (MLSS) and reflects the gold standard for the determination of the second or 'anaerobic threshold' [6,38,39].…”
Section: Phase Imentioning
confidence: 99%
See 1 more Smart Citation
“…During steady-state exercise, this leads to an equilibrium in BL appearance and BL elimination. The highest workload, which can be performed for about 30 min without a systematic increase in the BL concentration, is called 'maximal lactate steady state' (MLSS) and reflects the gold standard for the determination of the second or 'anaerobic threshold' [6,38,39].…”
Section: Phase Imentioning
confidence: 99%
“…Three-line regression concepts have incorporated the two LTs into one graph [11]. The 'second lactate turn point' was shown to correlate well with MLSS [38,39] and approximates a BL level of 4 mmol/l [29,15]. The important point in favor of this threshold fixation, however, seems the convenience of a whole number.…”
Section: Controversial Terminologymentioning
confidence: 99%
“…These authors showed that despite minimal heart rate differences of only 5 b·min −1 between two rowing exercise bouts just below or above VT 2 , growth hormone response was almost doubled in exercise above the VT 2 . Given these findings, the second turn point for La, HR, or VE [29, 30, 65, 71, 76], consistent with the maximal lactate steady state [67, 76], seems to be a criterion for the upper level of exercise prescription in healthy subjects and patients.…”
Section: Exercise Intensity Prescription By Means Of Submaximal Mamentioning
confidence: 99%
“…Normwerte liegen unter Ruhebedingungen im Bereich von 4-6ml/Schlag und steigen unter maximaler Belastung auf etwa 10-20ml/Schlag an (Wonisch 2003 (Smith, Johnson et al 1993). Die Einnahme von Betablockern bei bestehender Herzinsuffizienz führt, bedingt durch die reduzierte Herzfrequenz, zu höheren Absolutwerten des Sauerstoffpulses auf der jeweiligen Belastungsstufe (Wonisch, Hofmann et al 2002).…”
Section: Sauerstoffpulsunclassified